Midostaurin added to chemotherapy and continued single-agent maintenance therapy in acute myeloid leukemia with FLT3-ITD - Schlenk, Richard Friedrich; Benner, Axel (Blood, 2019)
Patients with acute myeloid leukemia (AML) and a FLT3 internal tandem duplication (ITD) have poor outcomes to current treatment. A phase 2 hypothesis-generating trial was conducted to determine whether the addition of the multitargeted kinase inhibitor midostaurin to intensive chemotherapy followed by allogeneic hematopoietic cell transplantation (alloHCT) and single-agent maintenance therapy of 12 months is feasible and favorably influences event-free survival (EFS) compared with historical controls. Patients 18 to 70 years of age with newly diagnosed AML and centrally confirmed FLT3-ITD were eligible: 284 patients were treated, including 198 younger (18-60 years) and 86 older (61-70 years) patients. Complete remission (CR) rate, including CR with incomplete hematological recovery (CRi) after induction therapy, was 76.4% (younger, 75.8%; older, 77.9%). The majority of patients in CR/CRi proceeded to alloHCT (72.4%). Maintenance therapy was started in 97 patients (34%): 75 after alloHCT and 22 after consolidation with high-dose cytarabine (HiDAC). Median time receiving maintenance therapy was 9 months after alloHCT and 10.5 months after HiDAC; premature termination was mainly a result of nonrelapse causes (gastrointestinal toxicity and infections). EFS and overall survival at 2 years were 39% (95% confidence interval [CI], 33%-47%) and 34% (95% CI, 24%-47%) and 53% (95% CI, 46%-61%) and 46% (95% CI, 35%-59%) in younger and older patients, respectively. EFS was evaluated in comparison with 415 historical controls treated within 5 prospective trials. Propensity score-weighted analysis revealed a significant improvement of EFS by midostaurin (hazard ratio [HR], 0.58; 95% CI, 0.48-0.70; P < .001) overall and in older patients (HR, 0.42; 95% CI, 0.29-0.61). The study was registered at www.clinicaltrials.gov as #NCT01477606.
Gesehen am 24.07.2019